2012
DOI: 10.1128/aac.05953-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically and Clinically Diagnosed Vertebral Osteomyelitis: Impact of Prior Antibiotic Exposure

Abstract: We retrospectively reviewed medical records to identify the factors that affect the results of culture in patients with pyogenic vertebral osteomyelitis. In multivariate analysis, the presence of paravertebral abscess was associated with positive results of microbiologic culture. Prior antibiotic exposure, especially of longer duration, was strongly associated with negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 16 publications
2
42
3
2
Order By: Relevance
“…The prevalence of multidrug-resistant bacteria was low in our population. In fact, only one strain of S. aureus was methicillin resistant, which contrasts with previous studies, in which MRSA has been reported in 19.2 to 53.3% of cases of PVO (20)(21)(22)(23)(24)(25)(26). Similarly, we did not isolate any extended-spectrum ␤-lactamase (ESBL)-producing Enterobacteriaceae, which is inconsistent with recent data showing an increase in resistant strains of Enterobacteriaceae.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalence of multidrug-resistant bacteria was low in our population. In fact, only one strain of S. aureus was methicillin resistant, which contrasts with previous studies, in which MRSA has been reported in 19.2 to 53.3% of cases of PVO (20)(21)(22)(23)(24)(25)(26). Similarly, we did not isolate any extended-spectrum ␤-lactamase (ESBL)-producing Enterobacteriaceae, which is inconsistent with recent data showing an increase in resistant strains of Enterobacteriaceae.…”
Section: Discussioncontrasting
confidence: 56%
“…In acute hematogenous osteomyelitis, the blood cultures are positive in about 58 % of cases (Mylona et al 2009). Specimens for microbiological analysis should be taken prior to the antibiotic therapy to increase the yield probability (Kim et al 2012). If antibiotic therapy has already been established, the consideration should be made to withhold antibiotics for several days prior to microbiological sampling when feasible (Zimmerli 2010).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…It is well known that the yield of open surgical biopsy is higher than that of needle biopsy (9-11). Also, a higher CRP level occurs more frequently in patients with culture-positive PVO (3,12,13). One might expect that the longer the antibiotic-free period is, the higher the culture positivity rate is because more antibiotic would be removed from tissue and the negative effect of antibiotic exposure would be lessened.…”
mentioning
confidence: 99%
“…Prior antibiotic exposure has been reported in some studies to have a negative effect on microbiologic diagnosis (2)(3)(4)(5). In view of this, it is recommended that, for clinically stable patients, biopsy be delayed until at least 48 h after the last antibiotic has been administered (6).…”
mentioning
confidence: 99%